Missional Congregations in Civil Society: An Imagination for God's World. Issue 2 (June 2015) - Dreier, Mary Sue Dehmlow
Abstract This article provides glimpses of the emerging missional church within the civil society arena from the perspective of congregational case studies. Civil society studies offer five potential community contributions that provide congregations expanded possibilities for discerning and fulfilling their missional vocations in their communities. Framed within trinitarian missional theology, these create a meaningful framework for congregations to expand their imaginations and strengthen their public participation with God's mission in today's world.